Study on Strength and Deflection of Beams Using Metakaolin and Shredded Plastic Waste as Cement and Coarse Aggregate Replacer - Sivaraj, M.; R. Sundararajan, Dr.; T. Senthil Vadivel, Dr. (International Journal of Engineering and Technology, 2018)
Concrete is a composite material made from cement, water, fine aggregate and coarse aggregate. But present researchers are in interest of finding new cementing materials by waste materials or waste products produced from industries.Â Metakaolin is a cementitious material used as an admixture to produce high strength and is used for maintaining the consistency of concrete. The usage of plastics is increasing day by day although steps were taken to reduce its consumption. This creates substantial garbage every day which is much unhealthy. The cement is partially replaced by metakaolin (2.5%, 5%, 7.5% and 10% by weight) to improve the strength, durability and reduces the porosity of concrete. Also, it is the best way of environmentally friendly disposal of plastic. The properties of materials (Physical & Chemical) were studied meanwhile the strength characteristics (M20) such as compressive strength, split tensile strength and flexural strength test results were found by casting cubes, cylinders, prisms and beams.Â Â